The Human and the Divine : Aspects of Sanctity in Time and Space - Ulanowski, Krzysztof, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
This volume offers detailed insights into both familiar and overlooked aspects of how humans engage with sanctity and the divine in various cultures of Mesopotamia, the Mediterranean, and Beyond. Each chapter is dedicated to a specific theme-whether a region or phenomenon-from Prehistoric times to the Modern era, exposing readers to a whirlwind of impressions presented by individuals who have studied or been captivated by particular subjects. Framing the individual case studies are broader presentations by the editors, who highlight key issues with the aim of reviving a multidisciplinary dialogue and encouraging reader participation.